The Role and Importance of Armenia-NATO Partnership in the Context of the RA Military-Political Securit - Ghevondyan, Alen (Bulletin of Yerevan University D: International Relations and Political Sciences, 2018)
The article presents the different aspects of the historical, progressive and political partnership between the Republic of Armenia and NATO. The article considers that Turkish and Russian factors have a direct impact on Armenia-NATO relations. The article analyses the approaches of NATO towards the Nagorno-Karabakh settlement process, particularly it refers to the wording of the declarations. The article explores all the aspects of Armenia-NATO relations and the implementation of NATO-Armenia Individual Partnership Action Plans.